The Effect of Baby Massage on Body Weight and Sleep Quality of Babies Aged 3-6 Months - Sofi Ayu Rahmawati; Rukmaini; Shinta Novelia (Health and Technology Journal (HTechJ), 2024)
Midwives have the authority to monitor and stimulate the growth and development of babies and children. One form of growth and development stimulation carried out is baby massage. Some of the benefits of baby massage include increasing appetite and sleeping better. This study aims to determine the effect of baby massage on increasing the weight and sleep quality of babies aged 3-6 months. The design used in this research is quasi-experimental. Of the 32 babies, 16 were in the experimental group who received treatment, namely being given baby massage, and 16 were in the control group who were not treated. Research results show 16 respondents received massage treatment from test results of Paired T Test obtained a value <0.001, which means there is an effect of baby massage on the weight of babies aged 3-6 months at Griya Apressa in 2023. Research results: In the experimental group given massage treatment from 16 respondents, test results Wilcoxon Signed Rank Test Asymp value is obtained. Sig. 0,000, which means that baby massage influences the sleep quality of babies aged 3-6 months. Conclusion: Baby massages influence the weight and sleep quality of babies aged 3-6 months. It is hoped that further research will develop this research so that more variables are studied on the benefits of baby massage.